The transcription elongation factor ELL2 is specifically upregulated in HTLV-1-infected T-cells and is dependent on the viral oncoprotein Tax - Mann, Melanie; Strobel, Sarah; Fleckenstein, Bernhard; Kreß, Andrea (Virology, 2014)
The oncoprotein Tax of human T-cell leukemia virus type 1 (HTLV-1) is a potent transactivator of viral and cellular transcription. Here, we identified ELL2 as the sole transcription elongation factor to be specifically upregulated in HTLV-1-/Tax-transformed T-cells. Tax contributes to regulation of ELL2, since transient transfection of Tax increases ELL2 mRNA, Tax transactivates the ELL2 promoter, and repression of Tax results in decrease of ELL2 in transformed T-lymphocytes. However, we also measured upregulation of ELL2 in HTLV-1-transformed cells exhibiting undetectable amounts of Tax, suggesting that ELL2 can still be maintained independent of continuous Tax expression. We further show that Tax and ELL2 synergistically activate the HTLV-1 promoter, indicating that ELL2 cooperates with Tax in viral transactivation. This is supported by our findings that Tax and ELL2 accumulate in nuclear fractions and that they co-precipitate upon co-expression in transiently-transfected cells. Thus, upregulation of ELL2 could contribute to HTLV-1 gene regulation.
EVALuna2:8235